1998
DOI: 10.1091/mbc.9.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing and Ca2+-binding Activity of Dense-Core Vesicle Polypeptides inTetrahymena

Abstract: Formation and discharge of dense-core secretory vesicles depend on controlled rearrangement of the core proteins during their assembly and dispersal. The ciliate Tetrahymena thermophila offers a simple system in which the mechanisms may be studied. Here we show that most of the core consists of a set of polypeptides derived proteolytically from five precursors. These share little overall amino acid identity but are nonetheless predicted to have structural similarity. In addition, sites of proteolytic processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 54 publications
2
62
0
4
Order By: Relevance
“…Regulated secretory proteins form a vesicle core that was described as a dynamic aggregate (45,46). After their synthesis in the ER, regulated secretory proteins are sorted and segregated into secretory granules as soluble proteins; inside the vesicles, these proteins are converted to a temporarily insoluble form and finally reassembled after exocytosis, adopting a most stable structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulated secretory proteins form a vesicle core that was described as a dynamic aggregate (45,46). After their synthesis in the ER, regulated secretory proteins are sorted and segregated into secretory granules as soluble proteins; inside the vesicles, these proteins are converted to a temporarily insoluble form and finally reassembled after exocytosis, adopting a most stable structure.…”
Section: Discussionmentioning
confidence: 99%
“…In Tetrahymena thermophila and Paramecium tetraurelia, for example, the vesicle core synthesis occurs by assembly of soluble proteins into an insoluble, well organized lattice (46,57). It was proposed that in both microorganisms, this process involves binding of extracellular ionic calcium to regulated secretory proteins (46,58).…”
Section: Discussionmentioning
confidence: 99%
“…In tndl cells, 45Ca2+ binding of several bands is reduced in gel overlays, the precise genetic basis remaining to be established. In Tetrahymena, this Ca 2 + sensitivity develops during proteolytic processing of mucocyst content (Verbsky and Turkewitz, 1998). Any Ca 2 +-dependent biosynthetic processes during maturation thus can be exeuted without internal "explosion."…”
Section: Secretory Content Dischargementioning
confidence: 99%
“…During exocytosis, the secretory proteins are rapidly extruded, due to the fact that the crystalline lattices expand rapidly and directionally. Thus, the function of secretory organelles in ciliates depends upon the assembly of protein crystals that can undergo spring-like elongation (20,21).The most abundant proteins stored in and released from Tetrahymena mucocysts belong to two families, called GRT (for granule tip) and GRL (for granule lattice) (22,23). Studies of the Grl proteins, and the related P. tetraurelia tmp proteins, have demonstrated that extensive proteolytic processing occurs during mucocyst and trichocyst synthesis (20,(24)(25)(26).…”
mentioning
confidence: 99%
“…Thus, the function of secretory organelles in ciliates depends upon the assembly of protein crystals that can undergo spring-like elongation (20,21).…”
mentioning
confidence: 99%